Collaborative decision-making in multi-buy food purchases. (10th April 2019) - Anderson, Craig G.; Reid, Louise A.
Abstract: This research presents a quasi-experiment utilizing an original card-game to investigate aspects implicated in the creation of food waste in the UK, including over purchasing due to a lack of advanced planning as well as susceptibility to advertising multi-buy offers. A card game embedding a clear trade-off between the temptation of additional gain and the risk of waste was devised. Decisions to purchase different multi-buy offers were recorded across individual and group decision-making. The results indicate that collaborative purchase decision-making could have some impact on the way in which the risk of waste is dealt with, consistent with social signaling and collective action. Compared to individual decision-making, group decision-making saw a deferral in choices to purchase multi-buy offers with an associated risk of wastefulness wen only a moderate temptation was added. These differences were embedded in both planned strategies and revealed behavior. Food waste is linked to marketing practices as well as household routines and perceived levels of control, particularly amongst households with multiple young adults. Shopping is typically conducted as an individual, however collaborative shopping experiences may help with planning and control, particularly amongst a student population. Graphical abstract: Image 1011 Highlights: Household routines, multi-buy offers, and planning control can create food waste. Results from a card game experiment show deferral of waste in group decision-making. Collaborative shopping could reduce waste particularly in student housing.